Resident satisfaction with facilities and maintenance of low-cost housing apartment in Kedah - Abdul Ghani, Muhammad Amirul Hakim (2022)
Housing is a basic need for every human which come with basic infrastructure such as road and public transportation accessibility, electricity and water supply and other necessities which help in enhance the standard of living. Nowadays, there are many housings scheme that were provided by government, one of it is low-cost housing apartment. It appears because of massive urbanisation across the world. Low-cost housing apartment has comparatively low selling prices or rentals to keep the low income group's affordability high. However, to measure whether the government's housing program's success, the housing condition and facilities must meet the demands and needs of the occupant. For this reason, this study aim is to study on resident satisfaction towards facilities and maintenance of low-cost housing apartment in Kedah. The objective of this study is to discover the elements of facilities and maintenance available in low-cost apartment, to identify the level of resident satisfaction towards facilities and maintenance of low-cost housing apartment, and to determine a key factor of an improvement that can enhance the resident satisfaction level on facilities and maintenance.